"The day you lose your hope is the day you start to die": Quality of life measured by young women with metastatic breast cancer. Issue 4 (3rd July 2020) - Ginter, Amanda C.
Abstract: Purpose/Objectives: The number of young women with metastatic breast cancer (MBC) is growing in the United States. The intersection of age and cancer stage presents unique challenges for this population. However, there is little extant research on the concerns and perspectives of young women with MBC. The purpose of this study is to understand how young women describe their lived experiences following their diagnoses of MBC. Design: A cross-sectional qualitative study with a life course theoretical framework was employed. Sample/Participants: Purposive sampling yielded nine participants who took part in semi-structured interviews. Phenomenology informed understanding of the lived experience of young women with MBC. Findings: The findings describe how young women with MBC measure quality of life, via themes of facing off-time diagnoses, strategizing disclosure, relying on mindfulness and spirituality, contemplating the future, and differentiating surviving from truly living. Conclusion: The notion of short-term or long-term decision-making is clouded by a metastatic prognosis. Implications for Psychosocial Providers: These findings present new information about the needs of young women with MBC, with potentially transferable implications for young adults with other forms of metastatic cancer.